Spatial Memory and Blindness: The Role of Visual Loss on the Exploration and Memorization of Spatialized Sounds - Setti, Walter; Cuturi, Luigi F.; Cocchi, Elena; Gori, Monica (Frontiers in Psychology, 2022)
Spatial memory relies on encoding, storing, and retrieval of knowledge about objects’ positions in their surrounding environment. Blind people have to rely on sensory modalities other than vision to memorise items that are spatially displaced, however, to date, very little is known about the influence of early visual deprivation on a person’s ability to remember and process sound locations. To fill this gap, we tested sighted and congenitally blind adults and adolescents in an audio-spatial memory task inspired by the classical card game ‘Memory’. In this research, subjects (blind, n = 12; sighted, n = 12) had to find pairs among sounds (i.e., animal calls) displaced on an audio-tactile device composed of loudspeakers covered by tactile sensors. To accomplish this task, participants had to remember the spatialized sounds’ position and develop a proper mental spatial representation of their locations. The test was divided into two experimental conditions of increasing difficulty dependent on the number of sounds to be remembered (8 vs 24). Results showed that sighted participants outperformed blind participants in both conditions. Findings were discussed considering the crucial role of visual experience in properly manipulating auditory spatial representations, particularly in relation to the ability to explore complex acoustic configurations.